Upaya Meningkatkan Literasi Membaca Melalui Pojok Baca Untuk Mengantisipasi Buta Huruf Bagi Anak-Anak Di Desa Doda - Rahmat Rahmat; Eliarni S.T Rantenay; Syamsul Bahri Dg.Parani; Erwan Sastrawan (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This community service was carried out by Tadulako University lecturers and students in Doda Village, Kinovaro District, Sigi Regency. There is one thing that is the focus of the community service work program in Doda Village, namely a culture of low community literacy. The high number of school-age children is not accompanied by adequate literacy facilities. So that the literacy movement in Doda Village only relies on facilities and support from schools. The creation of a reading corner aims to provide literacy facilities and form reading habits in order to increase interest in reading as part of the literacy movement in Indonesia. The implementation of community service activities begins with observation, then is carried out in stages, namely social reflection, program planning, program implementation and evaluation. As an effort to form reading habits in order to foster children's interest in reading, assistance is provided for reading activities at the reading corner of Doda Village, Kinovaro District, Sigi Regency. The result of this service is the growth of children's interest in reading in Doda Village, this can be seen from the high enthusiasm of the children during the reading assistance activities which are carried out every week. It is hoped that this community service activity will foster children's interest in reading as an effort to activate the literacy movement in Indonesia.